2014
DOI: 10.1161/circresaha.114.302168
|View full text |Cite
|
Sign up to set email alerts
|

AKAP150 Contributes to Enhanced Vascular Tone by Facilitating Large-Conductance Ca 2+ -Activated K + Channel Remodeling in Hyperglycemia and Diabetes Mellitus

Abstract: Rationale Increased contractility of arterial myocytes and enhanced vascular tone during hyperglycemia and diabetes may arise from impaired large conductance Ca2+-activated K+ (BKCa) channel function. The scaffolding protein AKAP150 is a key regulator of calcineurin (CaN), a phosphatase known to modulate expression of the regulatory BKCa β1 subunit. Whether AKAP150 mediates BKCa channel suppression during hyperglycemia and diabetes is unknown. Objective To test the hypothesis that AKAP150-dependent CaN signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
165
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(178 citation statements)
references
References 41 publications
(59 reference statements)
11
165
1
1
Order By: Relevance
“…Previous reports have shown that in vitro, short term exposure of coronary, cerebral, and mesenteric arteries to extracellular glucose concentrations that resemble diabetic hyperglycemia (e.g. 20 mM) inhibit K V and BK Ca channel activity in VSMCs (11)(12)(13)(14)(15). Thus, inhibition of these channels may contribute to enhanced arterial tone and vascular complications during diabetes.…”
mentioning
confidence: 98%
“…Previous reports have shown that in vitro, short term exposure of coronary, cerebral, and mesenteric arteries to extracellular glucose concentrations that resemble diabetic hyperglycemia (e.g. 20 mM) inhibit K V and BK Ca channel activity in VSMCs (11)(12)(13)(14)(15). Thus, inhibition of these channels may contribute to enhanced arterial tone and vascular complications during diabetes.…”
mentioning
confidence: 98%
“…Diabetes mellitus reduces BK channel activity by ≥3 mechanisms. First, as demonstrated by Nystoriak et al, 2 through activation of calcineurin, dephosphorylated nuclear factor of activated T cells, c3 isoform (NFATc3) enters the nucleus where it inhibits transcription of the β1 subunit of BK, thereby reducing BK sensitivity to calcium. Second, diabetes mellitus-induced elevations in reactive oxygen species (ROS), particularly hydrogen peroxide, directly oxidize cysteine residues in the bowl region of the α subunit of BK to reduce opening.…”
Section: Disclosuresmentioning
confidence: 99%
“…AKAPs play roles in many more cellular processes whose dysregulation leads to disease. They are involved in complex mechanisms such as memory formation and blood pressure control [161,262,263] and tether different protein assemblies to various subcellular compartments [264]. Thus AKAPs are a rich source to be considered as pharmacological targets.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 99%